Potentiality and Model for Personnel Development of Thai Health Tourism Industry (in order) to Professional Framework Effectiveness - Ma-oon, Ranumas; Sukonthasab, Suchitra; Leemingsawat, Wipawadee (Academic Journal of Thailand National Sports University, 2018)
Tourism industry has a major role in Thailand’s economic system, especially the Health Tourism which had trend to be a great need of tourists from Asia countries. Thus, it is needed to have the standard model for development of high competency and desirable characteristics of human resources for Health Tourism, which the key aims for high efficiency management in Health Tourism. This study, entitle “Potentiality and Guidelines for Personnel Development of Thai Health Tourism Industry (in order) to Professional Framework Effectiveness” aimed to:- 1) examine types, personality, and characteristics for working of human resources for health tourism, 2) study competencies for working of human resources for health tourism, both Core Competency, Specific Competency and Functional Competency, 3) develop the standard model for human resources of health tourism development, and 4) propose the standard model for human resources of health tourism development . The research procedure divided into the mixed methods design were applied for phase one, which were survey questionnaires for 180 human resources of health tourism and 1600 foreign tourists participating in health tourism attraction, and qualitative research using in- depth interview for 60 health tourism specialists and academic health professions. For phase two, the research and development design was applied for developing the standard model based on the result from the phase one. The major finding was the developed standard model for human resources of health tourism development, which presented in term of the human resources of health tourism development center. This center consisted of four units, which were :- (1) Public Relation & Information Services Unit, (2) Standard Competency Testing & Evaluation Unit, (3) Human Resources Management & Development Unit, and (4) Professional Framework Certification Unit. Both of four units have to work together based on systematic approach concept, based on government policy and law. The government has to establish the specific organization, which was the Thailand Professional Qualification Institute (Public Organization) to be the responsibility organization. So, it can be concluded that the standard model can promote Health Tourism human resources for high effectiveness Health Tourism management.